ANALISIS PERANAN COST CONTROLLER DALAM PENGENDALIAN BIAYA OPERASIONAL DAN PENDAPATAN OPERASIONAL PADA HOTEL MERCURE MANADO TATELI BEACH RESORT - Uhise, Esterlin; Manossoh, Hendrik; Suwetja, I Gede (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The purpose of this study is to determine whether the role of cost controller in operational costs and operating income goes well or not at Mercure Manado Tateli Beach Resort hotel. The data used to analyze the role of cost controller that is qualitative data, while based on the source using primary and secondary data. The method used in this research descriptive method, which aims to provide a clear picture of the object of research. The results showed that the role of cost controller in the control of operational costs and operating income at Mercure Manado Tateli Beach Resort hotel is running well and in accordance with the SOP Keywords: Cost controller, Operational Cost, Operating Income